Pengawasan Penangkapan Ikan di Zona Ekonomi Eksklusif Indonesia dalam Membangun Poros Maritim Indonesia - Nurfaika Ishak; Siti Fatimah (Wacana Hukum, 2019)
Indonesia is a maritime country that has an abundance of marine natural resources, especially fisheries resources. The wealth of Indonesian fisheries resources should be managed in such a way as to be able to provide benefits for the greatest prosperity of the people (in accordance with the mandate of the 1945 Constitution). Normatively, Law Number 31 Year 2004 which has changed with Law Number 45 of 2009 concerning Fisheries, has been regulated regarding the management of fisheries in Chapter XII Article 66-70. The urgency of supervision in the fisheries sector is intended so that all regulations can be implemented in accordance with what has been determined. But in reality there are so many deviations in the aspects of management and protection of fisheries resources especially in the fishing process. Crimes and violations that occur such as Illegal, Unreported, and Unregulated Fishing activities result in very large material losses reaching Rp.101,040 trillion / year. In addition to material losses, Indonesia also suffered other losses in the form of invaluable environmental damage to violations of sovereignty limits.